Use of the Theoretical Domains Framework to explore factors influencing paediatric fever management practices and antipyretic use in New Zealand emergency departments. (23rd July 2022) - Tan, Eunicia; Haskell, Libby; Beck, Sierra; MacLean, Alastair; Rogan, Alice; Than, Martin; Venning, Bridget; White, Christopher; Yates, Kim; McKinlay, Christopher JD; Dalziel, Stuart R
Abstract : Aim: To explore factors influencing fever management practices and antipyretic use among New Zealand Emergency Department (ED) doctors and nurses using the Theoretical Domains Framework (TDF). Methods: Cross‐sectional survey of doctors and nurses across 11 New Zealand EDs. The questionnaire examined eight of 12 TDF domains, based on a generic questionnaire validated to assess TDF‐based determinants of health‐care professional behaviour. Relevant domains were identified by the frequency of beliefs; the presence of conflicting beliefs within a domain; and the likely strength of impact of a belief on paediatric fever management in the ED. Results: About 602 participants (243 doctors, 353 nurses and 6 unknown) completed the survey (response rate 47.5%). Over half (351/591, 59.6%, 95% confidence interval (CI) 55.5–63.5%) knew the content of clinical practice guidelines regarding antipyretic use in febrile children (TDF Domain Knowledge), or had been trained to ensure antipyretics are given to febrile children only if they appear distressed (347/592, 58.6%, 95% CI 54.5–62.6%) (Skills). Over 40% (246/590, 95% CI 37.7–45.8%) aim to reduce the fever before discharge (Goals). Most (444/591, 75.1%, 95% CI 71.4–78.6%) participants felt capable of explaining appropriate antipyretic use to parents/care givers (Beliefs about Capabilities). Only a minority (155/584, 26.5%, 95% CI 23.0–30.3%) thought that they can ensure antipyretics are given to febrile children only if they appear distressed when the ED is busy (Environmental Context and Resources). Conclusions: Using the TDF, we identified factors influencing fever management practices and antipyretic use in the ED. These factors can guide the design of targeted, theory‐informed knowledge translation strategies.